Analisis Capital Expenditure, Foreign Independent Directors, dan Manajemen Risiko Terhadap Nilai Perusahaan - Andhika, Muhammad Andhika M; Endah, Endah Susilowati (Akuntansi: Jurnal Akuntansi Integratif, 2023)
Indonesia, known as the country with the largest natural resource potential in the world, especially in the energy sector, is an important contributor to Non-Tax State Revenue. The main source of this income in Indonesia comes from the energy sector, especially the oil and gas and mining sub-sectors. In this context, it is very important for companies that manage energy resources to increase their value, so that they can continue to carry out research and development related to these resources. This research aims to examine and show the influence of capital expenditure, foreign independent directors, and risk management on the value of companies operating in the oil and gas and mineral and coal sub-sector in Indonesia, which are listed on the Indonesia Stock Exchange (BEI) during the 2016-2020 period. This research uses quantitative descriptive research methods, with multiple linear regression analysis as the analysis technique. The sample selection method used was purposive sampling, with a total of 95 samples. The research results show that capital expenditure and risk management have a significant effect on company value. However, foreign independent directors do not have a significant influence on firm value. The implication of this research is that companies can increase investment in capital assets and implement risk